Strategi Penanaman Nilai-Nilai Religius Peserta Didik Pada Era Revolusi Industri 4.0 di SMP N 1 Sukakarya Kabupaten Bekasi - Wahyuni Tirta Dewi; Mimin Maryati; Hinggil Permana (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
Education is a sector that needs to be developed in order to creat a developed country. The era of the industial revolution 4.0 is a challenge for the education sector, especially education in Indonesia. There are so many students in Indonesia who are influenced by foreign cultures due to the rapid development of the 4.0 Industrial Revolution Era, this requires the cultivation of religious values to balance the development of the 4.0 Industrial Revolution Era. In this study, researchers used a qualitative method that aims to describe the data in the form of facts that occur in the field, whit interview data collection techniques. Based on the results of interviews with Curriculum teachers, it was found that the startegy for impelementing religious values in the Industrial Revoulusion 4.0 Era carried out at SMP N 1 Sukakarya was to instill habituation in religious activities, apply regulations to teachers so that as an ecample for students, and the involvement of ROHIS extracurricular activities in the context of implementing religious values at SMP N 1 Sukakarya.